2013
DOI: 10.1364/ome.3.000309
|View full text |Cite
|
Sign up to set email alerts
|

Solution-processing of thick chalcogenide-chalcogenide and metal-chalcogenide structures by spin-coating and multilayer lamination

Abstract: This paper presents a new technique for fabricating thick (>10µm) chalcogenide multilayer structures. Films of arbitrary thicknesses are readily achieved through spin-coating, lamination and baking. For homogeneous systems, layer interfaces can be effectively removed by annealing above T g. Alternatively, heterogeneous multilayer films can be realized by introducing layers of different chalcogenide materials or metals. In particular, photo-induced Ag dissolution is verified in a laminated multilayer film, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…For instance, the response of solution-deposited arsenic sulfide to light shows signs of approaching the bulk material, in terms of an increase of the refractive index as well as densification [32]. In other studies, researchers found photodarkening and photo-induced Ag diffusion in spin-coated As-S, As-Se and Sb-S films which were consistent with evaporated materials [32,[39][40][41][42]. Furthermore, photo-induced linear dichroism was shown in spin-coated arsenic selenide films, with a value even larger than evaporated films [39], which could be associated with the larger "free volume" in spin-coated films.…”
Section: Chemical Structures and Light Exposurementioning
confidence: 89%
“…For instance, the response of solution-deposited arsenic sulfide to light shows signs of approaching the bulk material, in terms of an increase of the refractive index as well as densification [32]. In other studies, researchers found photodarkening and photo-induced Ag diffusion in spin-coated As-S, As-Se and Sb-S films which were consistent with evaporated materials [32,[39][40][41][42]. Furthermore, photo-induced linear dichroism was shown in spin-coated arsenic selenide films, with a value even larger than evaporated films [39], which could be associated with the larger "free volume" in spin-coated films.…”
Section: Chemical Structures and Light Exposurementioning
confidence: 89%
“…Residual solvents in these lms can be eliminated by a short, hard baking step at 90 C. It has been established that further annealing at 170 C for a few hours ensures re-polymerization of ChG and thus lms with structural properties similar to that of bulk ChG glass can be achieved. [13][14][15]35 It is observed that lms annealed at 50 C for two hours followed by annealing at 80 C for another two hours result in most defect free lms (mean surface roughness # 2 nm) which can later be reinforced structurally by a hard baking step at 170 C for 2 hours. Two subsequent annealing steps ensure removal of solvent slowly without causing defects at rst and then re-bonding of the ChG molecules so that the lms regains structural properties similar to bulk glass.…”
Section: Film Preparationmentioning
confidence: 99%
“…[7][8][9][10][11] Earlier, these thin ChG lms were created with thermal evaporation mostly, but now solution processed ChG lms are beginning to show signicant advantages on lms deposited thermally. 1,2,[12][13][14][15][16][17][18][19][20][21][22] It has been shown that various amine solvents dissolve ChG via nucleophilic substitution of sulphide or selenide units with amine groups and may prove to be ideal for creating thin lms and structures for photonic, electronic or imaging application. 12,15,23 Physical, optical and structural properties of solution processed (SP) ChG lms have been found to be at par with thermally deposited lms if complimented with appropriate annealing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, many of the photoinduced effects in ChGs are more pronounced in thin films rather than bulk glasses [1]. For instance, silver photodoping of As 2 S 3 films improves the material photosensibility [6].…”
Section: Introductionmentioning
confidence: 99%